Effectiveness of Digital Health Intervention in Enhancing Medication Adherence Among Arthritis Patients: A Systematic Review of Randomized Controlled Trials (Nepal Journal of Epidemiology, 2024)
Background:  Arthritis affects millions of people worldwide, however its mismanagement remains a growing global challenge, resulting in reduced quality of life(QoL) and disability. Digital health (DH), including smartphones, could be the key to solving this problem. Specific evidence-based reviews on the use of DH in this context is lacking. Hence, this systematic review aimed to explore the effect of DH on medication adherence(MA) among arthritis patients, thus improving their QoL.Methods: A literature search was done on PubMed, Cochrane, TRIP and Google Scholar, using keywords: digital health, medication adherence and arthritis. All randomised controlled trials (RCT) published between 2006 and 2024 were assessed for eligibility.Results: The literature search yielded 12,671 results with 882 duplicates. The review included 8 RCTs which addressed rheumatoid arthritis(N=5), gout(N=2) and juvenile idiopathic arthritis(N=1), with a total sample size of 2449 patients, among which 66% were males. Digital interventions used include calls, texts, videos and online counselling. Study outcomes were classified as positive (DH increased MA), no significant difference and negative (DH failed to show an effect on MA) in 62.5%, 25% and 12.5% of the studies respectively.Conclusion: This systematic review concluded that 62.5% of the included RCTs showed significant contributions of digital health tools in arthritis management, mainly by enhancing medication adherence and thus improving patients' QoL. The ubiquitous and indispensable nature of smartphones in modern society highlights their effectiveness as a channel to reach patients, and promote medication adherence. Owing to their availability, simplicity, and immediacy, digital health tools demonstrate their potential as reliable interventions for supporting arthritis patients. Future research could aim to include a larger and more heterogeneous population, over an extended study duration.